Modified Laparoscopic Nephron-Sparing Surgery for Large Renal Hilar Angiomyolipoma: Dual-Center Experience - Yang, ZeSong; Wang, Fang; Lin, Deng; Li, Qiuyan; Hong, Yun; Hu, Minxiong; Zhang, Dahong; Ye, Liefu (Frontiers in Surgery, 2022)
Objective: The aim of this study is to evaluate a potential successful strategy for treating large renal hilar angiomyolipoma (RHAML) during the procedure of laparoscopic nephron-sparing surgery (NSS). Methods: The total study population includes 12 patients with large RHAMLs who underwent laparoscopic NSS in the department of urology of Fujian Provincial hospital and People's Hospital of Zhejiang, ranging from January 2016 and March 2020. The perioperative variables, intraoperative procedure, and post-procedure complications were all recorded. Three months later, all patients returned to the hospital to check their postoperative recovery by reviewing the computed tomography urography (CTU) image. In following-up, patients were asked to have their review by CT or color doppler ultrasound every year. Results: Laparoscopic NSS was successfully performed in all patients. The average operation time was 113.33±33.39 minutes; The intraoperative blood loss was about 137.50±91.17 ml; The warm ischemia time was 25.25±4.88 minutes; The drainage tube extubation time was 4.58±2.07 days, and the hospital stay time was 6.42±1.78 days. The average follow-up time was 14.58±9.18 months. After 3 months, all CTU images showed an unobstructed urinary tract in the patient, and no tumor recurrence was found. In addition, no patients had renal atrophy and urine extravasation during follow-up. Conclusions: Laparoscopic NSS for RHAML is complex and technically demanding, but good surgical design and operation can achieve satisfactory surgical results. Modified laparoscopic NSS was a beneficial technique and may provide a reference for the treatment in patients with RHAML.